Agrobacterium tumefaciens-induced proteomic remodelling and physiological adaptations in Hypericum perforatum L - Preeti Shakya; Rajendran K. Selvakesavan; Dawid Perlikowski; Vimala Antonydhason; Leonard Kiirika; Gregory Franklin (Plant Stress)
Despite the widespread use of Agrobacterium tumefaciens-mediated transformation in plant genetic engineering and functional genomics, many economically and industrially important crops, especially medicinal plants, are resistant to A. tumefaciens-mediated T-DNA transfer and have proven difficult to improve with this technique. Here, we report, for the first time, the proteomic and physiological changes in a pharmaceutically important and non-transformable medicinal plant, Hypericum perforatum, in response to A. tumefaciens using a comprehensive proteomic approach and physiological assessments. Proteome analysis of H. perforatum cells challenged with A. tumefaciens via liquid chromatography/tandem mass spectrometry revealed 1200 differentially expressed proteins (DEPs; 613 up-regulated and 587 down-regulated) after 12 h and 390 DEPs (174 up-regulated and 216 down-regulated) after 24 h of co-cultivation. Functional analysis revealed early activation of the key defence-related protein PR-10, indicating rapid pathogen recognition and initiation of defence responses. Simultaneously, antioxidant enzymes, such as peroxiredoxin and l-ascorbate peroxidase, were significantly up-regulated, indicating robust attenuation of oxidative stress. The induction of cell wall-modifying proteins, such as UDP-arabinopyranose mutase and pectin acetylesterases as well as accumulation of proteins related to secondary metabolic defence mechanisms, such as phenylalanine ammonia lyase, 1,3,7-trihydroxyxanthone synthase, and benzophenone synthase, indicated a coordinated plant defence response. Physiological analysis also revealed significant stress responses in H. perforatum seedlings, including reduced photosynthetic performance and stomatal changes as early as 12 h, which intensified after 24 h. Taken together, the identified key proteins and altered physiological responses of H. perforatum contribute to the understanding of factors underlying recalcitrance of plants to Agrobacterium-mediated transformation.